Maybe next time : a novel - Major, Cesca (William Morrow, an imprint of HarperCollinsPublishers, 2023)
"One Day meets Groundhog Day, in this heartwarming and emotionally poignant novel about a stressed woman who must relive the same day over and over, keeping her family and work life from imploding as she attempts to spare her husband from an unfortunate fate"--